Strengthening Religious Character through Hijaz Yamani Poetry as a Source for Social Science Learning - Bambang Subiyakto; Jumriani Jumriani; Mutiani Mutiani; Muhammad Adhitya Hidayat Putra; Ersis Warmansyah Abbas (STAI Hubbulwathan Duri, 2022)
Moral degradation is still a central issue in educational practice. Responding to these problems, making character education a solution to improve students' morality. Character education design focuses on 18 values that are mandated to be integrated into learning. One of these values is religious value. This article aims to analyze the poetry of local writers to be used as social studies learning resource. This research is a type of semiotic research. As semiotics is a type of research that emphasizes the aspect of extracting the meaning of signs in a literary work. The collection of data used in this research is a library study. The data analysis technique was carried out based on the semiological analysis of Roland Barthes. The study results describe the religious characters contained in the collection of poems in the form of depictions of Aqidah, Sharia and Morals. Religious character is strongly influenced by the strengthening of Islamic values in society. Thus, it is a concern in the practice of social studies learning that religious characteristics originating from Islam affect social life. This relates to several materials, namely class VIII Chapter IV Changes in Indonesian Society during the Colonial Period and the Growth of National Spirit. This material describes that the struggle of the Indonesian people and the spirit of nationalism grew because of their religious character. The integration of poetry as a social study learning resource strengthens the existence of religious characters. Religious character does not discriminate against the existence of other religions. However, providing diversity to achieve and practice religious teachings in harmony.